Identification and validation of the molecular subtype and prognostic signature for clear cell renal cell carcinoma based on neutrophil extracellular traps - Quan, Jing; Huang, Banggao (Frontiers in Cell and Developmental Biology, 2022)
Background: Renal cell carcinoma (RCC) is one of the most common cancers, with an annual incidence of nearly 400,000 cases worldwide. Increasing evidences also demonstrated the vital role of neutrophil extracellular traps (NETs) in cancer progression and metastatic dissemination. Methods: Consensus cluster analysis was performed to determine the number of ccRCC subtypes. Kruskal-Wallis test or student t-test was performed to evaluate the difference of infiltrating immune cell and gene expression in different groups. Kaplan-Meier (KM) method was used to draw the survival curve. LASSO cox regression analysis was conducted to construct a NETs-related prognostic signature. We also constructed a LncRNA-miRNA-mRNA regulatory axis by several miRNA and lncRNA target databases. Results: A total of 23 differentially expressed NETs-related genes were obtained in ccRCC. Three clusters of ccRCC cases with significant difference in prognosis, immune infiltration and chemotherapy and targeted therapy were identified. LASSO cox regression analysis identified a NETs-related prognostic signature including 6 genes (G0S2, DYSF, MMP9, SLC22A4, SELP, and KCNJ15) and this signature had a good performance in predicting the overall survival of ccRCC patients. The expression of prognostic signature genes were significantly correlated with pTMN stage, immune infiltration, tumor mutation burdens, microsatellite instability, and drug sensitivity of ccRCC patients. MMP9 was identified as the hub genes. Wo also identified lncRNA UBA6-AS1/miR-149-5p/MMP9 regulatory axis for the progression of ccRCC. Conclusion: Collectively, the current study identified three molecular clusters and a prognostic signature for ccRCC based on neutrophil extracellular traps. Integrative transcriptome analyses plus clinical sample validation may facilitate the biomarker discovery and clinical transformation.